A Kaleckian approach to financialization and distribution: Austria and Finland in comparison - Dabrowski, Cara; Kuhls, Sonia (Wirtschaft und Gesellschaft, 2025)
In this paper, we examine if and to what extent the Kaleckian theory of markup pricing can explain changes in functional income distribution in an environment of financialization. Following this approach, we expect financialization to influence the aggregate wage share through three channels: (1) sectoral recomposition, (2) financial overhead costs and rentiers’ profit claims, and (3) bargaining power of trade unions and workers. We empirically analyse the long-term trends for each of the channels before and after the Global Financial Crisis and the Great Recession for Austria and Finland. Overall, we find evidence for all three redistribution channels contributing to the changes in functional income distribution. However, the explanatory power of the individual channels differs strongly due to the heterogeneity of the countries.